Steady-State Performance Analysis of a Variable Tap-Length LMS Algorithm - Yonggang Zhang; Ning Li; Chambers, J.A.; Sayed, A.H. (IEEE transactions on signal processing, 2008)
A steady-state performance analysis of the fractional tap-length (FT) variable tap-length least mean square (LMS) algorithm is presented in this correspondence. Based on the analysis, a mathematical formulation for the steady-state tap length is obtained. Some general criteria for parameter selection are also given. The analysis and the associated discussions give insight into the performance of the FT algorithm, which may potentially extend its practical applicability. Simulation results support the theoretical analysis and discussions.